Pharmacokinetic and tissue distribution studies of cassane diterpenoids, in rats through an ultra‐high‐performance liquid chromatography–Q exactive hybrid quadrupole–Orbitrap high‐resolution accurate mass spectrometry. (11th July 2019) - Wang, Miao; Wang, Da; Gao, Changjiu; Li, Xianzhe; Sha, Luping; Zhao, Qiang; Gao, Huiyuan; Wu, Zhaohua
Abstract: Cassane diterpenoids (CA) are considered as the main active constituents of medicinal plants belonging to the Caesalpinia genus. Three cassane derivatives, bonducellpin G (BG), 7‐ O ‐acetyl‐bonducellpin C (7‐ O ‐AC) and caesalmin E (CE), isolated from Caesalpinia minax Hance seeds, showed strong anti‐inflammatory activity. In this paper, pharmacokinetics (BG, 7‐ O ‐AC, CE) and tissue distribution (7‐ O ‐AC, CE) properties were studied for the first time using a reliable, sensitive and rapid UHPLC–Q‐Orbitrap HR‐MS to develop new anti‐inflammatory agents. A novel quantitative method with full scan in positive ion mode was used to determine the contents of compounds. They were separated using acetonitrile–water (0.1% formic acid) as gradient mobile phase. The calibration curve displayed good linearity and the lower limit of quantitation was 0.005–0.02 μg/mL for all analytes. Meanwhile, the absorption, distribution, metabolism, excretion (ADME) property was predicted using PreADMET web. The pharmacokinetic parameters indicated that they were absorbed quickly, eliminated rapidly together with high blood concentration. The results of tissue distribution demonstrated that CE was distributed rapidly and widely among tissues, and stomach was the main tissue site of CE and 7‐ O ‐AC, followed by small intestine/liver. This study indicates that the structures and dosages of active CA should be modified to help improve the absorption rate and residence time, and the findings are helpful for the pharmaceutical design of CA derivatives.